PERANAN DAN TANGGUNG JAWAB NOTARIS DALAM KEPASTIAN PROSES PENGESAHAN BADAN HUKUM - DEDY AHMAD WIRYADI (PREMISE LAW JURNAL, 2016)
SABH (Legal Entity Administrative System) is used to request the settlement of the legal entity of a corporation electronically by using internet online. A Notary as a public official not only serves people who need his service but also because of law. The Notary’s responsibility in the establishment of a  corporation cannot be separated from his role in the process of the validation of the establishment of the corporation. A Notary’s knowledge should be in line with technological advancement in using SABH. SABH is used to replace inefficient manual system in the procedure of validation of the establishment of a Corporation; but, for many reasons, manual system is still in effect besides SABH which is not in line with the previous regulation which states that manual system is not in effect. By using SABH, it is expected that there will be no obstacle any more in the practice of validating a corporation to become legal entity since it has good control system so that human error can be decreased because all processes operate automatically. Keywords        :           Notary, Validation of Corporation, Legal Entity Administrative System